Lone Star legacy - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Forever Texas novel, 2023)
In 1854 South Texas, Regis Royle, while trying to turn eighteen-thousand acres of raw prairie land into the greatest cattle ranch in the world, must fight for his dream when the powerful Valdez family claims rights to his land and will kill to get their hands on it.